2018
DOI: 10.3389/fimmu.2018.00745
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Peroxisome Proliferator-Activated Receptor Gamma and the Canonical WNT/β-Catenin Pathway in Chronic Inflammation and Oxidative Stress During Carcinogenesis

Abstract: Inflammation and oxidative stress are common and co-substantial pathological processes accompanying, promoting, and even initiating numerous cancers. The canonical WNT/β-catenin pathway and peroxisome proliferator-activated receptor gamma (PPARγ) generally work in opposition. If one of them is upregulated, the other one is downregulated and vice versa. WNT/β-catenin signaling is upregulated in inflammatory processes and oxidative stress and in many cancers, although there are some exceptions for cancers. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(200 citation statements)
references
References 283 publications
(288 reference statements)
5
194
0
1
Order By: Relevance
“…Another possible important modulators of PPAR activity is cellular stress, such as oxidative stress and endoplasmic reticulum (ER) stress. In many tissues, reactive oxygen species (ROS) activate the Wnt/β-catenin pathway, leading to PPARγ inactivation [97,98], whereas PPARγ agonists reduce ROS production and chronic inflammation and suppress the Wnt/β-catenin pathway [99]. PPARα signaling was found to prevent the induction of mitochondrial and ER stress and reduce the synthesis of apolipoprotein B, thus improving the hyperlipidemia and fatty degeneration of the liver that is related to fructose intake [100].…”
Section: The Other Factors Modulating Hepatic Ppar Functionmentioning
confidence: 99%
“…Another possible important modulators of PPAR activity is cellular stress, such as oxidative stress and endoplasmic reticulum (ER) stress. In many tissues, reactive oxygen species (ROS) activate the Wnt/β-catenin pathway, leading to PPARγ inactivation [97,98], whereas PPARγ agonists reduce ROS production and chronic inflammation and suppress the Wnt/β-catenin pathway [99]. PPARα signaling was found to prevent the induction of mitochondrial and ER stress and reduce the synthesis of apolipoprotein B, thus improving the hyperlipidemia and fatty degeneration of the liver that is related to fructose intake [100].…”
Section: The Other Factors Modulating Hepatic Ppar Functionmentioning
confidence: 99%
“…Local immunity is also controlled by cell communications leading to an increase in tumour heterogeneity (7). In parallel to the heterogeneity of cancer cells, immune heterogeneity with tumour-associated macrophages (85) and tumour-infiltrating lymphocytes (86) has been established and defines an immune tolerant niche.…”
Section: Presence Of Cancer Stem Cells In Osteosarcoma: Their Functiomentioning
confidence: 99%
“…Different cancerous and developmental studies reported the cross-talk between Wnt/β-catenin pathway and the nuclear hormone receptor PPARs family [19,43]. PPARδ has been observed to regulate the BL development and implantation process in the mice uterus in response to Cox2 activation [44].…”
Section: Discussionmentioning
confidence: 99%